Congestion Management in Hybrid Electricity Markets with FACTS Devices with Loadability Limits - Ashwani Kumar Sharma (Institute of Advanced Engineering and Science, 2012)
Congestion management (CM) is one of the most important challenging tasks of the Independent System Operator (ISO) in the deregulated environment. In this paper, generators’ rescheduling based CM approach to manage transmission line congestion considering loadability limit has been presented for hybrid based electricity market model. The main contribution of the paper is (i) to obtain secure transactions for hybrid market model, (ii) optimal rescheduling of generators with loadability limits taken into account with secure transactions, (iii) and impact of FACTS devices on transmission line congestion management. The ISO ensures secure bilateral transactions in a hybrid market model and CM is managed with minimum preferred schedule to obtain minimum congestion cost. The results have been obtained for IEEE 24 bus test system. Keywords: Generator re-dispatch, congestion management, pool electricity market, bid function, loadability limit.DOI:http://dx.doi.org/10.11591/ijece.v2i1.114